Integrated Geophysical Evidence for the Middle-Lower Crust Melting of the Songpan-Aba Terrain, NE Tibetan Plateau - Zhao, Chongjin; Zhang, Luolei; Yu, Peng; Xu, Xi (Frontiers in Earth Science, 2021)
The Songpan-Aba region is located on the northeastern edge of the Tibetan Plateau. Tectonically, the area is surrounded by the West Qinling orogenic belt in the north, the Longmenshan orogenic belt in the southeast, and the East Kunlun and Sanjiang orogenic belts in the west and southwest, forming a triangle that provides an ideal location to study the crust-mantle structure and deep tectonics of the eastward extrusion of the Tibetan Plateau. In this study, the magnetic and electrical structures of the SongpanAba area were investigated by inversion using high-precision magnetic anomaly and magnetotelluric data to obtain the subsurface magnetization inversion intensity and resistivity of Songpan–Aba and adjacent areas. The results revealed a continuous magnetic layer up to 20 km below Songpan–Aba and its surrounding areas in the south, possibly originating from a magma root southwest of the Longmenshan massif. In the West Qinling, Songpan–Aba, and Longmenshan areas, pervasive low-resistance, weakly magnetic, or magnetic layers were identified below 20 km that might be formed from the molten mantle material extruded from the eastern edge of the Tibetan Plateau.